2015
DOI: 10.1007/s12010-015-1762-4
|View full text |Cite
|
Sign up to set email alerts
|

Caspases and Thrombin Activity Regulation by Specific Serpin Inhibitors in Bovine Skeletal Muscle

Abstract: In living cells, after activation, protein inhibitors constitute the last step of proteases activity regulation. This review intends to provide original information about a group of bovine muscle serine proteases inhibitors belonging to the Serpin superfamily and characterized at the gene and protein level. This report is the only one and the first to provide much information on this group of proteases inhibitors of the serpin type and their potential biological functions. Amongst the eight genes identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 94 publications
(164 reference statements)
4
12
0
1
Order By: Relevance
“…Accordingly, the positive correlations observed between PRDX6 and ENO3 or TPI1 involved in glycolysis, and a negative correlation with MDH1 involved in oxidative pathway, is coherent with the low abundance of PRDX6. In agreement with a previously proposed muscle-related regulation ( Gagaoua et al, 2015a ; Knoops et al, 1999 ), the study of ( Keady et al, 2013 ) comparing longissimus lumborum from Aberdeen Angus (AA) characterized by slow oxidative muscles, and Belgian Blue (BB) characterized by fast glycolytic muscles, observed higher abundance of metabolic enzymes involved in glycolysis and the citric acid cycle in AA vs. BB steers. Consequently, PRDX6 showed increased abundance in muscle of AA relative to BB steers.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, the positive correlations observed between PRDX6 and ENO3 or TPI1 involved in glycolysis, and a negative correlation with MDH1 involved in oxidative pathway, is coherent with the low abundance of PRDX6. In agreement with a previously proposed muscle-related regulation ( Gagaoua et al, 2015a ; Knoops et al, 1999 ), the study of ( Keady et al, 2013 ) comparing longissimus lumborum from Aberdeen Angus (AA) characterized by slow oxidative muscles, and Belgian Blue (BB) characterized by fast glycolytic muscles, observed higher abundance of metabolic enzymes involved in glycolysis and the citric acid cycle in AA vs. BB steers. Consequently, PRDX6 showed increased abundance in muscle of AA relative to BB steers.…”
Section: Discussionsupporting
confidence: 87%
“…Anti-viral roles for serine proteases have been identified in the airway, and serine proteases have been identified as drug targets for respiratory diseases, including virus infections [164,165]. Bovine serpins are cross-class inhibitors and shown to be strongly active against trypsin, as well as regulating caspases, therefore playing important roles in control of apoptosis in mammals [166]. In cow, serine proteases are for example involved in defences against Babesia bovis, a tick-borne and major apicomplexan pathogen in the cattle industry worldwide [167].…”
Section: Discussionmentioning
confidence: 99%
“…As Esserpin-3 is highly expressed in the gills, it may also function in host defense. In addition, it has reported that BovSERPINA3-1 and A3-3 (belonging to the Serpin superfamily) were located in muscle cells and are cross-class inhibitors strongly active against trypsin as well as against human initiator and effector caspases 8 and 3 (Gagaoua et al, 2015). Several results have tended to ascertain the onset of apoptosis in postmortem muscle, and the level of proteases inhibitor level is a better predictor of meat tenderness than their target enzyme (Boudida et al, 2014).…”
Section: Sequence Comparison and Phylogenetic Analysismentioning
confidence: 99%